Apical hypertrophic cardiomyopathy: contemporary view on the prevalence, clinical profile, diagnostic and treatmen (review of literature) - A. A. Streltsova; A. Ya. Gudkova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2021)
This review presents the last literature data, concerning prevalence, clinical profile, diagnostic and treatment of apical hypertrophic cardiomyopathy (HCM), as less known among «classical» variants of HCM. It is also discussed the rare form of apical HCM — mid-ventricular HCM with apical aneurism formation.